Flow-proof strategy in proof construction on geometry instruction. (July 2020) - Scristia; Hapizah; Sumarni; Araiku, J
Abstract: The purpose of this research is to assess the role of flowproof strategy implementation in improving students' mathematical proof in similarity and congruence. Proofing similarity and congruence is a prerequisite in developing mathematical skills. The subjects include prospective mathematics teachers, and the study used a qualitative descriptive technique. The implementation of the flow-proof strategy was achieved through four activities, including re-writing existed information, stating what is needed to be proved, using existed rules such as postulate and definition, and writing the results in flowcharts. The findings shows that flow-proof strategy on Geometry construction was implemented appropriately, based on students' performance in similarity and congruence proofs with percentage of 72% from all research subject.